On a transformation of the wiener process in ℝ^m by a functional of the local time type on a surface - Osipchuk, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A transformation of the Wiener process ξ_t in ℝ^m is considered. This transformation is realized by a multiplicative functional α_l = u(ξ_l/u(ξ_0), where the function u is constructed in a certain way by using a functional of the local time type on a surface. It is proved that this transformation is equivalent to the successive application of an absolutely continuous change of a measure and killing on the surface.